2013
DOI: 10.4028/www.scientific.net/ssp.198.226
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Lift Force of Mini Quadrotor Helicopter by Changing of Gap Size between Rotors

Abstract: This paper describes comparison between virtual simulation of quadrotor flying platforms (mini UAV - Unmanned Aerial Vehicle) and real experiments. In quadrotor helicopter (quadrocopter) air flows that are going out from rotors and affecting each other were simulated. Analysis of several helicopters that have different distances between rotors on different angular velocities were compared. During virtual simulation (with CFD Computational Fluid Dynamics software) there were conducted similar to real experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Simulations for lifting force determination and gap distance optimisation were made on the base of a simplified quadrotor helicopter model with 254 mm propellers. Separate simulations for four different rotation speeds 1500 min -1 , 3000 min -1 , 4000 min -1 and 5000 min -1 were done [35]. For each rotation speed, the distance range between the propellers changed from 5 mm to 140 mm ( Figure 11).…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulations for lifting force determination and gap distance optimisation were made on the base of a simplified quadrotor helicopter model with 254 mm propellers. Separate simulations for four different rotation speeds 1500 min -1 , 3000 min -1 , 4000 min -1 and 5000 min -1 were done [35]. For each rotation speed, the distance range between the propellers changed from 5 mm to 140 mm ( Figure 11).…”
Section: Simulationsmentioning
confidence: 99%
“…The work by [33] tried to save system energy by chattering reduction during mini UAV control. Work by [34,35] considered thrust optimisation in rotors with two and three propellers. The main purposes of this research are to consider the influence of rotor pitch and gap between rotors on lift force and power consumption of a quadcopter.…”
Section: Introductionmentioning
confidence: 99%
“…As for the flow field characteristics analysis of the quadrotor aircraft, Hwang et al [12] studied the interaction between the rotors and the fuselage of the quadrotor on the hover and forward flight by numerical simulation, and found that he inflow caused by the interaction of the rotors was higher than that of a single rotor. Aleksandrov et al [13] studied aerodynamic interference in hover with different spacing by comparing the result of experiment and CFD simulation. Nguyen et al [14] found that the lift coefficient of rear rotors was decreased obviously due to the interference from the front rotor with wind tunnel test.…”
Section: Introductionmentioning
confidence: 99%
“…Kaya et al [15] used momentum and blade element theory to deduce the expressions of forces and moments generated by the rotor, and verified them through wind tunnel tests. Aleksandrov et al [16] analyzed the aerodynamic interference between rotors at different rotor spacing by experiment and CFD simulation, but the influence of aerodynamic interference on power is not considered. Lei et al [17] studied the aerodynamic performance of coaxial rotor with different spacing and wind disturbance by wind tunnel tests.…”
Section: Introductionmentioning
confidence: 99%